Discovery of a potent HMG-CoA reductase degrader that eliminates statin-induced reductase accumulation and lowers cholesterol - Shi-You Jiang (Nature Portfolio, 2018)
Accumulated HMG-CoA reductase (HMGCR) limits the cholesterol-lowering effect of statins via a feedback loop. Here the authors developed a compound that degrades HMGCR, thus decreasing cholesterol levels and reducing atherosclerotic plaques.